Producing the academy school: an ethnographic study of failure, transformation, and survival in English secondary education - Pennacchia, Jodie (2017)
Academy schools have been the flagship education policy in England since 2000. The policy is controversial and its evidence base is contested, but it is also resilient and academy status continues to be extended to a greater number of schools. The claim to transform, which has played a pivotal role in the construction of academies in contexts of poverty, raises a set of ontological questions that have not yet been given the detailed consideration they require. The term ontology captures the nature of being, how particular entities come to exist, and how these shape the conditions of possibility with which we live. This thesis contributes to research on the academies policy by taking up this ontological direction of inquiry to analyse how academy status and the academy school are produced in underperforming schools in contexts of poverty. Combining Foucauldian discourse analysis and an ethnography of a secondary school – Eastbank Academy – it interrogates how the academy school is produced across different discursive spaces, and how this affects the identities and experiences of staff and students. Across four analysis chapters I attend to the linguistic, material, spatial, and pedagogical shaping of the failing school that becomes an academy, making a number of central arguments. First, academies are shaped as policy objects through a set of representations and truths that enable them to mesh with other social policy narratives that are flourishing in austere times. Second, academy status is renarrativised around the recognition of poverty in Eastbank, which is part of ethical relations between staff and students. Third, academy status creates a context of threat and surveillance in a failing school in a context of poverty, the trace of which can be read through the shifting visual, material, and spatial culture of Eastbank. Fourth, academy status is produced through pedagogical shifts that divide, categorise, and monitor, resulting in unjust and exclusionary learning experiences for some students. I combine these sub-findings to argue that academy status is produced in multi-modal ways, across which, a fluctuating, divisive, and fraught academy ontology emerges. This, in turn, produces increasingly fraught and divided identities for staff and students, and is implicated in unjust educational practices and experiences. I argue that this outcome is symptomatic of the delicate process of survival that marked the production of Eastbank Academy in the current education policy context. To conclude, I outline the implications of this study for knowledge of the academy school and the methodologies required to study education policy as a complex, shifting, and multi-modal entity. This thesis highlights some of the silenced possibilities for how academy status is produced in schools that are categorised as failing, presenting academy status as a disciplinary tool. It draws attention to the negotiated nature of academy status and how these negotiations play a pivotal role in young people’s experiences of schooling, in creating possibilities for resistance, and in creating unjust schooling practices. These are important considerations given the continued policy momentum to turn schools into academies.